Penerapan Persyaratan Teknis Pasar Tradisional: Studi Kasus Pasar Tawangmangu, Kota Malang - Rippa Sogawa, Putu; Soaduon Panjaitan, Tigor Wilfritz; Istijanto, Suko (Rifa'Institute, 2023)
Traditional markets are centers of economic activity that have the potential to drive an economy based on the people's economy. Therefore, it is necessary to fulfill technical requirements in order to maintain a comfortable and safe market image. The city government is planning a market revitalization program, but not much has been realized. Tawangmangu Market, Malang City, was the object of research using 25 aspects of the SNI technical requirements criteria for people's markets. Conditions in the market largely do not meet the technical requirements set, because several indicators of existing facilities and infrastructure do not function as intended. This study used descriptive qualitative method. Data collection by field observation and documentation of physical aspects. The research results show that there are 23 aspects of market requirements studied that have not been met and have not been used effectively.